Impact of Social and Microcredit Characteristics on Small Project Financing: A Case Study of Agricultural Entrepreneurial Firms in Sudan. - ALESSA, Adlah A; ZAABI, Elmoez Abdulmajid; DIAB, Amir Mohammed (African Scientific Journal, 2025)
Abstract Microfinance banks positively impact rural small business entrepreneurs. This study focused on microcredit’s effect on agricultural projects in Dongola-Souda. A survey of 120 agriculture entrepreneurs was conducted to gather their opinions on accessing bank loans and assistance. Results showed a strong connection between small business activities, private entrepreneurship, and microfinance from banks. Microfinance significantly benefited rural entrepreneurs with limited resources, enabling business establishment and success. It alleviated financial and non-financial constraints, supporting project maintenance. The study highlighted challenges posed by strict regulations, hindering ease of doing business and starting new ventures. It emphasized the need to improve administrative procedures and social aspects of microfinance for easier finance access and poverty reduction. In summary, microfinance banks positively impact small business financing and project achievement in rural areas. Improving administrative procedures and social aspects of microfinance is crucial for easier financial access and poverty alleviation. Key Word Entrepreneurship – Microfinance - Small business – Microcredit – Economy